ANALISIS MUTU DOSEN DALAM PERSPEKTIF REKRUTMEN (Studi Kasus di STAI Babussalam Sula Maluku Utara) - Hardiaman Usia; Abdul Wahab Hasyim; Marwan Man Soleman (Politeknik Negeri Lhokseumawe, 2023)
This study aims to determine the analysis of the quality of lecturers from the perspective of recruitment at STAI Babussalam Sula North Maluku, using several recruitment indicators, namely, objectives, stages, basis of determination, methods and factors, while on the quality of lecturers namely education and teaching, research and development and service to society. The type of research used is descriptive qualitative, and the data analysis used is an interactive model starting from reduction, data presentation and conclusion. The results of this study indicate that 1.) Recruitment of lecturers at STAI Babussalam Sula uses an open method, but in practice it has not fully followed the SOP. This is influenced by several factors, namely: a). STAI Babussalam Sula has not been able to enforce pure procedures, like state campuses, because all decisions are based on policies from the foundation. b). STAI Babussalam Sula is a campus at the district level and is still at the developing stage. c). Lecturer recruitment has not been based on needs analysis. 2). While the quality of lecturers in the Tridarma at STAI Babussalam Sula, namely: a). In education and teaching, there are still some non-linear lecturers who carry out the learning process for majors and study programs, and the availability of inadequate infrastructure. b). Research and community service carried out by lecturers is still minimal, this is influenced by the availability of an inadequate budget, because the financial source depends on student tuition fees. Keywords: Perspective, Lecturer Quality, Recruitment